Health Services in Health Centers Located Regions, Limitations, and Islands - Nikson Kristian Rahanra; S. Supriyanto; Hikmawan Suryanto (Health Notions, 2018)
The coverage and even distribution of health services, throughout the territory of the Republic of Indonesia particularly in Remote Areas, Border and Islands (DTPK) need to be improved. With the formulation of action plans and development plans by the Government, one of which is the strategy of the Ministry of Health of the Republic of Indonesia, 2015 is to increase the access of the Remote, Border and Islands (DTPK) communities to quality health services. This research was a descriptive observational research at Tanimbar Kei Public Health Center of Southeast Maluku District of Maluku Province. The study was conducted from March to June 2016. Data were collected through interviews with 93 community respondents and local community health centers at randomly selected. As well as the results of the author's observations during his work at the Health Office of Southeast Maluku District, also conducted a review of documents/policies, (literature). The amount of manpower is only 2 people that is 1 nurse educated School of Health Nurse (SPK) and Midwife. Facilities are also very lacking of medical equipment amounting to 10 and non medical amounting to 6 is 2 tables and 4 chairs. Remote Areas, Borders and Islands (DTPK) have extreme topography; The role of infrastructure is one of the important physical components for DTPK. There is a significant correlation between the condition of infrastructure and the socio-economic activities of the community, as well as the welfare of the people at the border; and the availability of health services and supporting facilities in remote areas, borders and islands (DTPK) is still low. Keywords: Health services, Public health center, Remote areas, Borders, Islands